Regulation and modulation of biogenic amine neurotransmission in Drosophila and Caenorhabditis elegans - Rosikon, Katarzyna D.; Bone, Megan C.; Lawal, Hakeem O. (Frontiers in Physiology, 2023)
Neurotransmitters are crucial for the relay of signals between neurons and their target. Monoamine neurotransmitters dopamine (DA), serotonin (5-HT), and histamine are found in both invertebrates and mammals and are known to control key physiological aspects in health and disease. Others, such as octopamine (OA) and tyramine (TA), are abundant in invertebrates. TA is expressed in both Caenorhabditis elegans and Drosophila melanogaster and plays important roles in the regulation of essential life functions in each organism. OA and TA are thought to act as the mammalian homologs of epinephrine and norepinephrine respectively, and when triggered, they act in response to the various stressors in the fight-or-flight response. 5-HT regulates a wide range of behaviors in C. elegans including egg-laying, male mating, locomotion, and pharyngeal pumping. 5-HT acts predominantly through its receptors, of which various classes have been described in both flies and worms. The adult brain of Drosophila is composed of approximately 80 serotonergic neurons, which are involved in modulation of circadian rhythm, feeding, aggression, and long-term memory formation. DA is a major monoamine neurotransmitter that mediates a variety of critical organismal functions and is essential for synaptic transmission in invertebrates as it is in mammals, in which it is also a precursor for the synthesis of adrenaline and noradrenaline. In C. elegans and Drosophila as in mammals, DA receptors play critical roles and are generally grouped into two classes, D1-like and D2-like based on their predicted coupling to downstream G proteins. Drosophila uses histamine as a neurotransmitter in photoreceptors as well as a small number of neurons in the CNS. C. elegans does not use histamine as a neurotransmitter. Here, we review the comprehensive set of known amine neurotransmitters found in invertebrates, and discuss their biological and modulatory functions using the vast literature on both Drosophila and C. elegans. We also suggest the potential interactions between aminergic neurotransmitters systems in the modulation of neurophysiological activity and behavior.